2016
DOI: 10.1186/s41240-016-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of major bacterial pathogens in aquaculture

Abstract: Background: Significant increases in the bacterial resistance to various antibiotics have been found in fish farms. Non-antibiotic therapies for infectious diseases in aquaculture are needed. In recent years, light-emitting diode technology has been applied to the inactivation of pathogens, especially those affecting humans. The purpose of this study was to assess the effect of blue light (wavelengths 405 and 465 nm) on seven major bacterial pathogens that affect fish and shellfish important in aquaculture. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…In accordance with these investigations, we also found endogenous porphyrins in the strains of USA 300, P aeruginosa ATCC 19660 and C albicans CEC 749 by fluorescence spectrometer and HPLC. Porphyrins are believed necessary for the majority of pathogens to utilize heme as an iron source that is essential for survival and pathogenesis of these bacteria and fungi , which explains the wide antimicrobial activities of blue laser spectrum (405‐470 nm) . The abundance of porphyrins generated in microbial cells is the reason behind the more susceptibility of all six representative microbes to 405 nm aBL irradiation than 470 nm, in agreement with the previous study showing that foodborne pathogens Lactobacillus plantarum , S aureus and Vibrio parahaemolyticus were all more susceptible to 405 nm than 460 nm or 520 nm light irradiation .…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with these investigations, we also found endogenous porphyrins in the strains of USA 300, P aeruginosa ATCC 19660 and C albicans CEC 749 by fluorescence spectrometer and HPLC. Porphyrins are believed necessary for the majority of pathogens to utilize heme as an iron source that is essential for survival and pathogenesis of these bacteria and fungi , which explains the wide antimicrobial activities of blue laser spectrum (405‐470 nm) . The abundance of porphyrins generated in microbial cells is the reason behind the more susceptibility of all six representative microbes to 405 nm aBL irradiation than 470 nm, in agreement with the previous study showing that foodborne pathogens Lactobacillus plantarum , S aureus and Vibrio parahaemolyticus were all more susceptible to 405 nm than 460 nm or 520 nm light irradiation .…”
Section: Discussionsupporting
confidence: 88%
“…Figure a demonstrates data for Gram‐positive isolates, with the dose required for a 1 log 10 reduction increasing for all organisms when wavelength is increased from 405–415 nm to 450–470 nm. The exception being the dose required for inactivation of Streptococcus inniae which decreased from 90.3 to 70.6 J cm −2 when wavelength was increased from 405 to 465 nm . The data for inactivation of Gram‐negative isolates (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…As demonstrated, the majority of the data sets (19/20) comparing the efficacy of violet-blue wavelengths found that increased doses were required for bacterial inactivation, or there was no inactivation achieved when using longer wavelengths between 450 and 470 nm. This is particularly pertinent in the case of Edwardsiella tarda with the dose for a 1 log 10 reduction increasing from 68.4 to 544.5 J cm À2 when wavelength increased from 405 to 465 nm (31), Entercoccus faecalis with the dose increasing from 130 to 410 J cm À2 when wavelength increased from 405 to 455 nm (39), Lactobacillus planterium with the dose rising from 374 to 1121 J cm À2 when wavelength increased from 405 to 460 nm (58) and L. monocytogenes with the dose rising from 61.6 to 1120.9 J cm À2 when the wavelength was increased from 405 to 450 nm (52) Therefore, although the analysis was made on a small selection of studies (n = 9), the general trend does support the current thinking that shorter wavelengths in the region of 405 nm are more effective for bacterial inactivation than longer wavelengths between 450 and 470 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roh et al successfully demonstrated the antimicrobial activity of 405 and 465-nm LEDs against major bacterial pathogens that affect fish and shellfish in aquaculture (Roh et al, 2016). Seven bacterial pathogens, including Vibrio anguillarum , Edwardsiella tarda , Aeromonas salmonicida , Vibrio harveyi , Photobacterium damselae , Streptococcus iniae , and Streptococcus parauberis , were studied.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%